2022
DOI: 10.1093/rb/rbac007
|View full text |Cite
|
Sign up to set email alerts
|

‘Invisible’ orthodontics by polymeric ‘clear’ aligners molded on 3D-printed personalized dental models

Abstract: The malalignment of teeth is treated classically by metal braces with alloy wires, which has an unfavorable influence on the patients’ appearance during the treatment. Herein, a modern treatment was tried using clear polymeric aligners, which were fabricated by molding a film material on the three dimensional (3D) printed personalized dental models. The key parameters of photocurable 3D printing of dental models and the mechanical properties of the clear aligner film material were investigated. Following a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…They found that the actual pore system in the polyisocyanate-based hydrogel was up to 3.7 μm, which may be insufficient for cell migration. However, the pore size of a scaffold can be well controlled and the global shape of a scaffold can be individually designed via 3D printing. ,, …”
Section: Discussionmentioning
confidence: 99%
“…They found that the actual pore system in the polyisocyanate-based hydrogel was up to 3.7 μm, which may be insufficient for cell migration. However, the pore size of a scaffold can be well controlled and the global shape of a scaffold can be individually designed via 3D printing. ,, …”
Section: Discussionmentioning
confidence: 99%
“…These additional treatments to accelerate polymer dissolution work well in labs, yet are unsuitable in many situations such as in hospitals where there is an instant demand. While much progress has been made in the fields of polymers and biomaterials, 45–52 the instant dissolution of a biomedical polymer in water has rarely been achieved. So far, no theory has been provided for the rapid dissolution of polymers without using additional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance value was measured at 570 nm using an Elx800 microplate reader. Cells without liposomes or free cytarabine treatment were used as a negative control, cell viability was calculated as (OD test group/OD control group) × 100% [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%